2001
DOI: 10.1111/j.1574-6968.2001.tb10571.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences betweenEscherichia coliO26 strains isolated in Brazil and in other countries

Abstract: Genomic diversity among 34 strains of Escherichia coli belonging to different serotypes of the O26 serogroup -- encompassing strains from different geographical origins and Shiga toxin-negative Brazilian strains -- was evaluated through random amplified polymorphic DNA (RAPD) analysis. Our results indicate that Brazilian and non-Brazilian O26 strains fall under distinct but closely related differentiation clusters. RFLP-PCR analysis of the fliC gene sequence was done in order to identify the H(-) serotypes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In fact, these serotypes and others with properties similar to those of O128:H2 are not true atypical EPEC or STEC serotypes but rather are heterogeneous serotypes that include different clones or genetic lineages. For example, we have recently shown by random amplified polymorphic DNA that O26:H11 Stx-producing strains isolated in Europe and North America are genetically different from Stx-negative strains of the same serotype isolated in Brazil ( 18 ). Although this kind of study has not been done with serotype O128:H2, this serotype is also heterogeneous since it includes different ribotypes with distinct virulence characteristics (L.R.…”
Section: Serotypesmentioning
confidence: 99%
“…In fact, these serotypes and others with properties similar to those of O128:H2 are not true atypical EPEC or STEC serotypes but rather are heterogeneous serotypes that include different clones or genetic lineages. For example, we have recently shown by random amplified polymorphic DNA that O26:H11 Stx-producing strains isolated in Europe and North America are genetically different from Stx-negative strains of the same serotype isolated in Brazil ( 18 ). Although this kind of study has not been done with serotype O128:H2, this serotype is also heterogeneous since it includes different ribotypes with distinct virulence characteristics (L.R.…”
Section: Serotypesmentioning
confidence: 99%
“…Recent findings in Brazil of E. coli O26 containing the H8 antigen belonging to EHEC and stx-negative strains led to the inclusion of this antigen in this study (45). Furthermore, antigen H11 and nonpathogenic antigen H32, commonly isolated in food products, were also tested (18,(45)(46)(47). Investigation of the H antigen revealed that all strains were positive for fliC H11 .…”
Section: Discussionmentioning
confidence: 99%
“…The typical and atypical EPEC strains selected for this study belong to the classical EPEC serogroups. We selected 10 aEPEC strains (two O26:H11, four O55:H7, one O111ab:H9, one O111:HNM, and two O119:H2) characterized by the eae ϩ EAF Ϫ genetic profile and expression of LAL in HEp-2 cells (6-h adherence assay) in previous studies (19,22,(26)(27)(28)(29). For comparison, three tEPEC strains (eae ϩ EAF ϩ ) belonging to the classical serogroups (O55:H6, O111:H2, and O119:H6) were also studied (19,26,27).…”
Section: Methodsmentioning
confidence: 99%